DETEKSI BAKTERI COLIFORM DAN ESCHERICHIA COLI DALAM SUSU KEMASAN YANG DISIMPAN PADA SUHU BERBEDA - Eliya Mursyida; Reny Guspratiwi (LPPM Universitas Abdurrab, 2019)
Milk is one food that contains nutritional value that is beneficial to the body, but is easily contaminated by several microbes. One of the microbes found in milk is Escherichia coli (E. coli) which is one of bacteria that causes diarrhea. E. coli strains produce endotoxins as virulence factors, causing disease. This study aims to detect Coliform and E. coli bacteria in packaged milk products stored at different temperatures. The design of this research is descriptive observational with total plate number (ALT) and Most Probable Number (MPN) test methods. Data were analysed descriptively, and presented in tbales and figures. The result obtained indicate that milk stores at room temperature contains bacteria with ALT 3.4x104CFU/mL and MPN values >1100/mL. so it can be concluded that the best temperature in pasteurized milk storage is at the refrigerator temperature.